Effect of Using Black Garlic Instead of Fresh Garlic in The Ration on The Performances and Blood Cholesterol Properties of Quail - Berliana Berliana; Nurhayati Nurhayati; Nelwida Nelwida; Raden Abdul Muthalib; Yun Alwi (Jurnal Agripet, 2023)
ABSTRACT. This study aimed to determine the effects of using black garlic (BG) instead of fresh garlic (FG) in the ration on the performances and quail blood cholesterol properties. Two hundred 3-week-old female quails were fed five experimental diets for 8 weeks. Each treatment was repeated four times with ten quails each. The treatment diets were: T0= commercial feed (CF) without FG and BG supplementation, T1= CF + 3% FG, T2= CF + 2% FG + 1% BG, T3= CF + 1% FG + 2% BG, and T4= CF + 3% BG. The parameters measured were feed consumption, egg production, egg weight, egg mass, feed conversion ratio, meat quality, and blood cholesterol properties. This study found no significant (P0.05) difference among treatment groups on feed conversion, egg weight, egg mass, total cholesterol, LDL, and HDL. Meat fat decreased significantly (P0.05) by increasing levels of dietary black garlic. A diet with black garlic supplementation significantly increased feed consumption, egg production, and meat protein (P0.05). It is concluded that substituting 100% garlic with black garlic in the diet could increase quail performance without adverse effects on blood cholesterol properties.(Pengaruh penggunaan bawang hitam sebagai pengganti bawang putih dalam ransum terhadap performa dan kadar kolesterol darah puyuh)ABSTRAK. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan bawang hitam (BG) sebagai pengganti bawang putih (FG) dalam ransum terhadap performa dan kolesterol darah puyuh. Dua ratus ekor puyuh betina berumur 3 minggu diberi pakan perlakuan selama 8 minggu dan diulang sebanyak empat kali. Setiap unit perlakuan terdiri dari sepuluh ekor puyuh. Pakan perlakuan adalah: T0= pakan komersial (CF) tanpa suplementasi FG dan BG, T1= CF + 3% FG, T2= CF + 2% FG + 1% BG, T3= CF + 1% FG + 2% BG, dan T4= CF + 3% BG. Parameter yang diukur adalah konsumsi pakan, produksi telur, berat telur, massa telur, rasio konversi pakan, kualitas daging, dan sifat kolesterol darah. Hasil penelitian memperlihatkan bahwa tidak ada pengaruh yang nyata (P0,05) antar kelompok perlakuan terhadap konversi pakan, bobot telur, massa telur, kolesterol total, LDL, dan HDL. Lemak daging menurun secara signifikan (P0,05) dengan peningkatan kadar bawang hitam dalam ransum. Pakan yang disuplementasi dengan bawang hitam nyata meningkatkan konsumsi pakan, produksi telur, dan protein daging (P0,05). Disimpulkan bahwa penggantian 100% bawang putih dengan bawang hitam dalam pakan dapat meningkatkan performa puyuh tanpa memberikan efek negatif terhadap kolesterol darah.